(3ebGJd GdWGdHjfs - (3CHh GdaQL Ydj Hf GdMSjf Hf eMeO GdCUagGfj,J (B356 (3g` s ((3eMeO Hf TQa GdOjf Hf GdMSf Hf YR GdOjf s)
(3ChdgG (B:s
(3bGd Ydi Hf GdMSjf GdCUagGfi GdeDda dgPG GdcJGH (B: (3HMeO Gddg hGdKfGA Ydjg jaJJM cd cdGe s
(3BNQgG (B:s
(3hcGf cd ef NGda gPg GdSHjd hbJd Ydi VOgG efge jSJJQ NHQg hfSCd Gddg GdYUeI hGdJhajb dWGYJghgh MSHfG hfYe Gdhcjd s
(3cJHJ GdYfhGfGJ HNW eLhOs
(3fbdJ Yf fSNI ecJhHI SfI (B616 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3JGQjN(B) s
Keywords: (3GdJGQjNs